Cutting sugar cane at Caroni, Trinidad, B.W.I. - (:unkn) unknown (Wilson and Johnstone, Trinidad, 2009)
A picture of an East Indian woman cutting the sugarcane for harvesting. Postcard numbered J359.
Colour: Black and White; Style: Portrait; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Sugarcane industry--Trinidad and Tobago; Sugarcane--Trinidad and Tobago; Working class--Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Caroni (Trinidad and Tobago : County) – Social aspects